2007
DOI: 10.1152/japplphysiol.00620.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coactivation of tongue protrusor and retractor muscles on pharyngeal lumen and airflow in sleep apnea patients

Abstract: The present study evaluated the effect of coactivation of tongue protrusors and retractors on pharyngeal patency in patients with obstructive sleep apnea. The effect of genioglossus (GG), hyoglossus (HG), and coactivation of both on nasal pressure (Pn):flow relationships was evaluated in a sleep study (SlS, n = 7) and during a propofol anesthesia study (AnS, n = 7). GG was stimulated with sublingual surface electrodes in SlS and with intramuscular electrodes in AnS, while HG was stimulated with surface electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 33 publications
2
62
0
Order By: Relevance
“…In these prior studies, investigators scrutinized EEG and ECG signals to exclude responses associated with cortical or autonomic activation (13,18,19). Additional studies with implantable nerve cuff (13) and fine-wire electrodes have demonstrated responses to selective lingual muscle stimulation during sleep and anesthesia (13)(14)(15)(16)(17). The present study also screened for evidence of cortical and autonomic activation, and further required strict temporal synchrony between the stimulus burst and airflow response to exclude arousal responses from the analysis.…”
Section: Arousalsmentioning
confidence: 99%
See 3 more Smart Citations
“…In these prior studies, investigators scrutinized EEG and ECG signals to exclude responses associated with cortical or autonomic activation (13,18,19). Additional studies with implantable nerve cuff (13) and fine-wire electrodes have demonstrated responses to selective lingual muscle stimulation during sleep and anesthesia (13)(14)(15)(16)(17). The present study also screened for evidence of cortical and autonomic activation, and further required strict temporal synchrony between the stimulus burst and airflow response to exclude arousal responses from the analysis.…”
Section: Arousalsmentioning
confidence: 99%
“…These increases have been attributed to decreases in pharyngeal collapsibility (14,16,17), which decreases the back pressure to inspiratory airflow (27). In previous studies, stimulating the genioglossus muscle and hypoglossal nerve led to an approximately 3-to 5-cm H 2 O decrease in critical pressure, which can account for an approximately 150-to 250-ml/s increase in maximal inspiratory airflow (18,19).…”
Section: Mechanism For Increased Airflow During Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, selective stimulation of both the lateral XII nerve branches and the medial nerve branch seems to increase maximum rate of airflow and mechanical stability [42,58,59]. Recent studies assessing efficacy of current commercial devices for electrical neurostimulation report significant improvement in AHI and quality of life measures [60][61][62].…”
Section: Osahs Treatmentmentioning
confidence: 99%